A Protocol Study to Establish Psychological Outcomes From the Use of Wearables for Health and Fitness Monitoring - Folkvord, Frans; van Breugel, Amy; de Haan, Sanneke; de Wolf, Marcella; de Boer, Marjolein; Abeele, Mariek Vanden (Frontiers in Digital Health, 2021)
Abstract Background: The last few decades people have increasingly started to use technological tools for health and activity monitoring, such as tracking apps and wearables. The main assumption is that these tools are effective in reinforcing self-empowerment because they support better-informed lifestyle decision-making. However, experimental research assessing the effectiveness of the technological tools on such psychological outcomes is limited. Methods and Design: Three studies will be conducted. First, we will perform a systematic review to examine the experimental evidence on the effects of self-tracking apps on psychological outcome measurements. Second, we will conduct a longitudinal field experiment with a between subject design. Participants (N = 150) begin a 50-day exercise program, either with or without the aid of the self-tracking app Strava. Among those who use Strava, we vary between those who use all features and those who use a limited set of features. Participants complete questionnaires at baseline, at 10, 25, and 50 days, and provide details on what information has been tracked via the platform. Third, a subset of participants is interviewed to acquire additional qualitative data. The study will provide a rich set of data, enabling triangulation and contextualization of the findings. Discussion: People increasingly engage in self-tracking whereby they use technological tools for health and activity monitoring, although the effects are still unknown. Considering the mixed results of the existing evidence, it is difficult to draw firm conclusions, showing more research is needed to develop a comprehensive understanding. Trial registration: Netherlands Trial registration: NL9402, received on 20 April 2021; https://www.trialregister.nl/trial/9402